Postoperative stereotactic radiosurgery for resected brain metastasis. (May 2014) - Ahmed, Zain; Balagamwala, Ehsan; Murphy, Erin; Angelov, Lilyana; Suh, John; Lo, Simon; Chao, Samuel
SUMMARY: Despite therapeutic advances in management, the prognosis of patients with brain metastasis remains dismal. Treatment options include surgical resection, whole brain radiation therapy (WBRT), and stereotactic radiosurgery (SRS). Patients who undergo surgical resection typically receive WBRT as adjuvant therapy. However, several studies have demonstrated an association between WBRT and neurotoxicity. Thus, clinicians are increasingly delaying WBRT in favor of postoperative use of SRS. In this review, we will discuss the current literature exploring the efficacy and toxicity of postoperative SRS in the treatment of patients with resected brain metastasis.